2020
DOI: 10.1038/s41598-020-76443-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally measured methane hydrate phase equilibria and ionic liquids inhibition performance in Qatar’s seawater

Abstract: Qatar has the third-largest natural gas reserves in the world and is the second largest Liquefied natural gas (LNG) exporter in the world. These reserves are mainly located in its offshore North Field where the gas is extracted, transported to the onshore units, and is converted to LNG for international export. The formation of natural gas hydrates in the offshore subsea lines can cause unwanted blockages and hinder the smooth supply of gas supply from offshore to onshore units. In the present work, the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Therefore, ions in the solution impede nucleation kinetics, as the driving force for hydrate crystallization reduces. Many studies have also reported that salts increase induction time. , For instance, Qureshi et al found that the induction time for ultrapure water was lower than that of seawater. Similarly, Pahlavanzadeh et al reported that the induction time was 5.1, 6.3, 17.2, and 21.3 min at NaCl concentrations of 0, 3.5, 5, and 8 wt %, respectively, for R410a hydrate.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ions in the solution impede nucleation kinetics, as the driving force for hydrate crystallization reduces. Many studies have also reported that salts increase induction time. , For instance, Qureshi et al found that the induction time for ultrapure water was lower than that of seawater. Similarly, Pahlavanzadeh et al reported that the induction time was 5.1, 6.3, 17.2, and 21.3 min at NaCl concentrations of 0, 3.5, 5, and 8 wt %, respectively, for R410a hydrate.…”
Section: Resultsmentioning
confidence: 99%
“…However, on the basis of the above experiments, the salts in seawater act as hydrate inhibitors. The presence of ions may reduce the availability of free water molecules in the system and may cause electrostatic interactions with the molecules, impeding the formation of gas hydrates and affecting the performance of hydrate promoters . Therefore, more research is needed, including advance computational modeling, nuclear magnetic resonance (NMR), Raman, and other in situ techniques, to understand the acting mechanism of l -tryp and 1,3-dioxane in saline systems.…”
Section: Resultsmentioning
confidence: 99%
“…As sodium chloride [NaCl] is a natural hydrate inhibitor, water-to-hydrate conversion is challenging to a greater extent in such saline systems. l -Tryptophan, a kinetic promoter that does not affect thermodynamic stability, , was tested to stimulate the formation of CO 2 hydrates . Based on earlier reported investigations with CO 2 hydrates, an optimum dosage of 500 ppm was chosen .…”
Section: Resultsmentioning
confidence: 99%